ANALISIS HASIL PEMERIKSAAN FISIK DAN LABORATORIUM DEMAM BERDARAH DENGUE DERAJAT I DAN II DI RSUD H. SAHUDIN KUTACANE TAHUN 2021 - Joharsah Joharsah; Fika Lestari; Purnama Sari Cane (Jurnal Maternitas Kebidanan, 2021)
Dengue fever is a severe fever that is often deadly, caused by a virus, characterized by capillary permeability, hemostasis abnormalities and in severe cases, shock syndrome loss of protein. The disease is divided into several degrees. To ensure patients suffer from DENGUE disease, it is necessary to perform physical and laboratory examinations such as hematology tests. This study aims to analyze the results of physical examinations and laboratories of DBD degrees I and II at H.Sahudin Kutacane Hospital. The study used descriptive methods with a Cross Sectional approach. Accidental sampling and the number of samples obtained is 20 respondents, among others, degrees I and II are 10 respondents. The data collection tool is carried out using observation sheets including demographic data, physical examination of DBD degrees I and II, and normal standard numbers and laboratory examination units of Amanah Kutacane Clinic. The results of research conducted from a physical examination of DBD degrees I and II show signs and symptoms of DENGUD disease that appear differently because in addition to the condition of a person's body response is different, It may also be because it has been given symptomatic and supportive treatment, while the laboratory results of DBD degrees I and II are only platelets whose value is low from normal numbers (150,000-450,000/μl) of 88,500/μl and 42,300/μl respectively and these laboratory results are affected by adequate fluid and oxygen intake and nutritious food intake so as to support proper administration of action/management